The effect of innovative work behaviour on the performance of service sector SMEs in Sabah / Siti Noraisah Musneh, Sylvia @ Nabila Azwa Ambad and Rosmimah Mohd Roslin - Musneh, Siti Noraisah; Ambad, Sylvia @ Nabila Azwa; Mohd Roslin, Rosmimah (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2021)
Innovation is often associated with the introduction of new products or services in the business. Moreover, it can also be about changing the way business is conducted. Innovation embraces new technologies, improves industry methods, meets changing customer demands or needs, and creates better systems and processes. The organisation relies heavily upon its stakeholders, especially the employees, when it wants to develop or create an innovative environment in the workplace, either in terms of operations, processes, or methods. In line with employees' innovative spirits, innovation is deemed more critical for Small Medium Enterprises (SMEs). As the backbone of Malaysia's economy, SMEs' competitive ability is often measured through its innovative capacity. In essence, SMEs and innovation are synergistically integrated as innovative efforts are regarded as the source of economic competitiveness. However, the means for the firms to be innovative remain questionable (Makanyeza & Dzvuke, 2016). In the current scenario, to achieve long-term success, an organisation needs to support and enhance its employees' innovative potential rather than focusing solely on research and development (R&D) professionals, scientists, or specialists. Thus, this study is conducted to examine the effect of innovative work behaviour on Sabah's SMEs' performance in the Service Sector. This is a quantitative research in which a total of 300 questionnaires were distributed to the managers of Service Sector SMEs in Sabah and 219 responses were received. The data collected was then analysed using PLS-SEM. This study found that the innovative work behaviour (β = 0.393, p =0.000) were positively related to organisation performance. Hence, innovative work behaviour is crucial to be embraced by the employees of the organisation itself to enable organisations to stay relevant in the industry and keep pace with the environment's rapid changes.